Oxaliplatin (3 months v 6 months) With 6 Months of Fluoropyrimidine as Adjuvant Therapy in Patients With Stage II/III Colon Cancer: KCSG CO09-07. Issue 33 (20th November 2022) - Kim, Seung Tae; Kim, Sun Young; Lee, Jeeyun; Yun, Seong Hyeon; Kim, Hee Cheol; Lee, Woo Yong; Kim, Tae Won; Hong, Yong Sang; Lim, Seok-Byung; Baek, Ji Yeon; Oh, Jae Hwan; Ahn, Joong Bae; et al.
Abstract : PURPOSE: The combination of oxaliplatin and fluoropyrimidine for 6 months is one of the standard options for adjuvant therapy for high-risk stage II and III colorectal cancers (CRCs). The optimal duration of oxaliplatin to diminish neurotoxicity without compromising efficacy needs to be clarified. PATIENTS AND METHODS: This open-label, randomized, phase III, noninferiority trial randomly assigned patients with high-risk stage II and III CRC to 3 and 6 months of oxaliplatin with 6 months of fluoropyrimidine groups (3- and 6-month arms, respectively). The primary end point was disease-free survival (DFS), and the noninferiority margin was a hazard ratio (HR) of 1.25. RESULTS: In total, 1, 788 patients were randomly assigned to the 6-month (n = 895) and 3-month (n = 893) arms, and 83.6% in the 6-month arm and 85.7% in the 3-month arm completed the treatment. The neuropathy rates with any grade were higher in the 6-month arm than in the 3-month arm (69.5% v 58.3%; P < .0001). The 3-year DFS rates were 83.7% and 84.7% in the 6-month and 3-month arms, respectively, with an HR of 0.953 (95% CI, 0.769 to 1.180; test for noninferiority, P = .0065) within the noninferiority margin. Among patients with stage III CRC treated by capecitabine plus oxaliplatin, the 3-year DFS of the 3-month arm was noninferior as compared with that of the 6-month arm with an HR of 0.713 (95% CI, 0.530 to 0.959; P = .0009). However, among patients with high-risk stage II and stage III CRC treated by infusional fluorouracil, leucovorin, and oxaliplatin, the noninferiority of the 3-month arm compared with the 6-month arm was not proven. CONCLUSION: This study suggests that adding 3 months of oxaliplatin to 6 months of capecitabine could be considered an alternative adjuvant treatment for stage III CRC (ClinicalTrials.gov identifier: NCT01092481 ).